Relevansi Bagian Warisan Sepertiga untuk Ayah dalam Kompilasi Hukum Islam - Aulia, M. Zulfa (Kontekstualita: Jurnal Penelitian Sosial Keagamaan, 2011)
This paper proposes the legal argumentation about legal basis of a fatherâs shares in the family inheritence (waris) as ratified in the Indonesiaâs Compilation of Islamic Law. Using Islamic Law theoretical framework, it challenges the popular misconception that is expressed in the compilation that a mother and children have one-third shares after fatherâs shares was given. Under this mode of thought, it is assumed that fatherâs and male family memberâs shares are bigger that that of motherâs and female family memberâs. In fact, it argues that the shares for all members of the family are the same: one-third.